Satisfação do cliente : estudo de caso na Cooperativa de Crédito Sicredi de Sarandi, RS - Ribeiro, Roberto Souza (2022)
This article refers to a survey carried out at Cooperativa de Crédito Sicredi, from the Municipality of Sarandi, RS. The main objective of the research was to analyze the relationship from the Sicredi branch in Sarandi, RS, with its associates, assessing satisfaction and loyalty arising from the commercial provision and services made available. Therefore, the research was developed in two stages: the first qualitative and exploratory, with the objective of generating the satisfaction indicators; and the second quantitative and descriptive, with the objective of measuring the co-workers' satisfaction. At the end of the study, with the analysis and interpretation of the results it was concluded that, in general, customers demonstrated satisfaction or great satisfaction in all queries relating to the products and services available to customers, with with the exception of some notes made about the speed of service, especially online and in the application, and in cooperative education, which deserve greater attention from the institution.